Web service QoS Based Broker Architecture and Heuristic Algorithm applied for an Apartment Management system (International Journal of Engineering and Computer Science, 2017)
Web Services are based on distributed technology and provide standard means of interoperating between different software applications across and within organizational boundaries. Web Services technologies allow interaction between applications. Sometimes a single service given alone does not meet user’s needs. In this case, it is necessary to compose several services in order to achieve the user’s goal. Quality of Service (QoS) support in web services plays a great role for the success of this emerging technology. In this paper, we presentQoS broker- based architecture for web services. The main goal of the architecture is to support the client in selecting web services based on his/her required QoS It also presents an efficient method to finding the suitable web service based on the consumer’s requirements along with QoS. We intend to use this architecture for several services like Loan system,location based search etc.